(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
In this study, a combination of qualitative and quantitative research designs was used to examine the innovation of turning squash into squash halaya. The integration of both approaches allowed the researchers to gather in-depth insights and measurable data, providing a well-rounded perspective on the product’s development. This methodological choice highlights how the design, structure, and implementation of a study can significantly influence research outcomes, especially when evaluating food innovations. This study utilized both qualitative and quantitative research designs to examine how the planning, organization, and implementation of a study can influence its findings—particularly in the context of innovating squash into squash halaya. The research involved fifty (50) Grade 12 Home Economics students as respondents. A stratified random sampling technique was employed to ensure fair and representative selection from the population. The majority of the respondents were between 17 and 18 years old. A total of 41 participants, accounting for 82% of the sample, represented a balanced mix of male and female students. Most were from sections HECF1201, HECF1202, HECF1203, and HEHRS1201. In terms of taste, the respondents rated the squash halaya as Very Much Acceptable, particularly highlighting its sweetness, buttery flavor, and creaminess. For texture, it was also rated Very Much Acceptable, especially in terms of spreadability, smoothness, and softness. Regarding appearance, the product was rated Acceptable for its uniqueness, shiny surface, and overall attractiveness. Based on their feedback, the following improvements were recommended: Increase the amount of squash to enhance flavor and consistency. Add food coloring to achieve a brighter and more appealing color. Adjust the quantity of coconut cream for better flavor balance. Add more milk powder to improve richness and creaminess. The findings of the study indicate that respondents generally agreed on the acceptability of the squash halaya as an innovative food product. In terms of taste, the product was rated Very Much Acceptable, particularly for its sweetness, buttery flavor, and creaminess. For texture, respondents also rated it Very Much Acceptable, emphasizing its smoothness, softness, and spreadable consistency. In terms of appearance, the product received an Acceptable rating, with positive remarks on its uniqueness, shiny surface, and visual appeal. Respondents also provided suggestions for improvement. These included: (1) increasing the amount of squash to enhance flavor and texture, (2) adding food coloring to create a brighter, more attractive appearance, (3) adjusting the amount of coconut cream to improve flavor balance, and (4) adding more milk powder to enrich the product’s taste and creaminess. Overall, the product was well-received, with feedback pointing to a strong foundation for further refinement and development.